Exploring Regional Differences in the Reading Competencies of Italian Students. (June 2014) - Matteucci, Mariagiulia; Mignani, Stefania
Background: Recently, the study of territorial differences in educational outcomes has assumed a particular importance for the policy strategies related to the socioeconomic conditions of different geographical areas. In Italy, international surveys for student assessments have introduced a regional stratification only recently, and regular national student assessments started only in 2008. Method: In this article, the reading performances of Italian students based on OECD-PISA 2009 are investigated, taking into account regional and macro-area partition. Student outcomes are explored by using a multilevel analysis, where school membership, socioeconomic and cultural background of students, and regional gross domestic product are introduced. Results: The results show that, despite the existence of a unified educational system in Italy, regional and macro-area differences in student reading achievements are consolidated and variability in performances among schools is especially noticeable. Comparisons based on national assessments by INVALSI at the end of compulsory school confirm these findings. Conclusion: Italian policy makers are advised to take into account these results to improve learning opportunities and to reduce educational gaps. In particular, targeted regional policies are needed to improve the mean performance especially in the Southern regions of Calabria, Campania, and Sicilia, and to strengthen the system equity in several regions, such as Emilia-Romagna. To decrease the school differences, possible suggestions are to postpone the choice of the school type (currently, at age 14) and to motivate good teachers to work in schools located in the worst socioeconomic and cultural environments.